INTEGRATION OF THE CONCEPTS OF PATIENCE AND RESILIENCE FROM THE PERSPECTIVE OF ISLAMIC PSYCHOLOGY: A SYSTEMATIC LITERATURE REVIEW - Mirnani Denta Athiyah Uchtiyani; M. Sholihin (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2026)
This study is motivated by the increasing mental health issues requiring an integrative approach between psychological and spiritual aspects. The concept of resilience in modern psychology has not fully accommodated the spiritual dimension, while the concept of sabr in Islamic psychology has the potential to serve as a foundation for individual resilience. This study aims to integrate the concepts of sabr and resilience within the perspective of Islamic psychology. The participants of this study were scientific articles obtained from academic databases that met the inclusion criteria. The method used was a systematic literature review following the PRISMA approach. The results indicate that sabr is closely related to resilience components such as emotional regulation, adaptability, and meaning-making. The integration of these concepts produces a theoretical framework positioning sabr as a spiritual foundation for resilience. These findings imply the development of Islamic-based psychological interventions.